Application of electrodialytic pilot plant for fluoride removal - Rangappa S. Keri; Kallappa M. Hosamani; Harisha R. Seetharama Reddy; Sanna Kotrappanavar Nataraj; Tejraj M. Aminabhavi (Химия и технология воды, 2011)
Removal of fluorine from water was investigated by electrodialysis method. In order to check the efficacy of ED unit, parameters like applied potential, pH; initial fluoride concentrations and flow rates were varied. Significant results were obtained with concentrations of less than 10 ppm. Results were satisfactory in meeting the maximum contaminate level (MCL) of 0.01 ppm for fluoride. Effect of working parameters on energy consumption was investigated using ion-exchange membranes. Results of this study are useful for designing and operating different capacities of ED plants for recovering different ions. The ED plant was found to be satisfactory to produce a good quality drinking water from the simulated mixture by removing the unwanted ions. Исследовано удаление фтора из воды методом электродиализа. Для проверки эффективности электродиализной установки варьировали приложенную разность потенциалов, начальную концентрацию фторида и скорость потока. Важные результаты были получены при начальной концентрации фторида <10 мг/дм3. С использованием ионообменных мембран исследовано влияние рабочих параметров на энергопотребление. Результаты данной работы будут полезны для разработки и планирования производительности электродиализной установки при выделении различных ионов. Электродиализная установка оказалась эффективной для получения питьевой воды хорошего качества из модельных растворов путем удаления нежелательных ионов. Досліджено видалення фтору з води методом електродіалізу. Для перевірки ефективності електродіалізної установки варіювали прикладену різницю потенціалів, початкову концентра цію фторидута швидкість потоку. Важливі результати були отримані при початковій концентрації фториду <10 мг/дм3. З використанням іонообмінних мембран досліджено вплив робочих параметрів на енергоспоживання. Результати цієї роботи будуть корисні длярозробки та планування продуктивності електродіалізної установки при виділенні різних іонів.Електродіалізна установка виявилася ефективною для отримання питної води хорошої якості з модельних розчинів шляхом видалення - небажаних іонів